2015
DOI: 10.1186/s12302-015-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socio-economic status and seasonal variation on municipal solid waste composition: a baseline study for future planning and development

Abstract: Background:The present study has highlighted the effects of seasonal variation and socio-economic status on generation and composition of municipal solid waste (MSW) in Shalimar Town (ST). The total amount of MSW generated in ST is estimated to be 927 tons per day per year. The average per capita rate of MSW collected in ST is 0.69 kg per day in all four seasons.Results: No significant difference was found in overall waste generation; however, statistical analyses show the significant difference for food waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 24 publications
9
29
3
2
Order By: Relevance
“…Thus, the lowest income group has higher generation rate of plastic than middle income group, while high income group generates the least amount of plastic as waste fraction. This trend is unique compared the findings in similar study in Lahore [40]. Moreover, more of this fraction was collected in winter and spring than in the other two seasons.…”
Section: Socioeconomic Influence On the Composition And Generation Racontrasting
confidence: 44%
See 2 more Smart Citations
“…Thus, the lowest income group has higher generation rate of plastic than middle income group, while high income group generates the least amount of plastic as waste fraction. This trend is unique compared the findings in similar study in Lahore [40]. Moreover, more of this fraction was collected in winter and spring than in the other two seasons.…”
Section: Socioeconomic Influence On the Composition And Generation Racontrasting
confidence: 44%
“…Although many similar studies have been conducted around in Pakistan and around the globe [16,19,36,[38][39][40][41], none have been conducted in Islamabad. The findings of this study can be used as Contemporary waste management literature/research and best practices suggest that shifting to a more environmentally friendly and sustainable waste management option requires an optimal combination of various management options such as recycling, composting, gasification, pyrolysis and incineration with energy recovery, instead of single waste management method [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the variation in the volume of waste collected by the IWCs, the author does not give the variation in the income in both seasons, as the study only revealed a daily earning of U.S$5-10 by the IWCs in the city. Kamran et al (2015) claim that, in Lahore, Pakistan, the average weekly waste collection by the IWCs in the wet and dry seasons was 1200 tons and 1050 tons, respectively. The dominant wastes in the wet and dry seasons were vegetable and rubber, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to an estimate, about 28 million tons of MSW is being produced annually in Pakistan, i.e., at a rate of 0.4 kg capita -1 day -1 . About 60% of the total produced waste in the country is organic or biodegradable (Kamran et al, 2015). This huge amount of waste is being dumped in open landfills along roadsides, railway lines, in empty plots and streets by municipalities or local waste producer.…”
Section: Introductionmentioning
confidence: 99%